Cannabidiol polarizes human neutrophils toward a cancer-promoting phenotype - Khoury, Mona; Hong, Yuxiang; Blokon-Kogan, Dayana; Gengrinovitch, Stela; Eitam, Harel; Avraham-Kelbert, Moran; Weinstein-Marom, Hadas; Xu, Peng; Cohen, Idan; Bar-Sela, Gil (Frontiers in Immunology, 2025)
IntroductionCannabidiol (CBD) is widely used as a natural alternative supplementary treatment for side effects and symptom relief in many diseases. Although the benefits and risks of using CBDs are still largely unknown, consumption has grown constantly.MethodsPrimary human neutrophils were isolated and exposed to CBD. Neutrophil functions such as oxidative burst, cytokine and chemokine production, bacterial killing, NET formation, and expression of cell surface markers were assessed. Conditioned media (CM) from cells treated with or without CBD were collected, and their impact on cancer cell proliferation, migration, and angiogenesis was examined. Furthermore, Neutrophil/T-cells co-culture was conducted to determine their effects on T-cell proliferation and activation.ResultsWe show that CBD induces human primary neutrophils to polarize into an N2-like cancer-promoting phenotype. CBD-exposed neutrophils exhibit reduced oxidative burst, reduce bacterial killing, and altered the production of cytokine and chemokine arrays like N2-polarized cells. CBD-treated cells also rapidly display a landscape of surface markers compatible with the described setup, known for N2-polarized cells, and promote cancer cell proliferation, migration, angiogenesis, and boost the expression of PD-L1 in cancer cells. Furthermore, CBD-stimulated neutrophils suppressed T-cell proliferation, suggesting that this signalling pathway may be involved in regulating T-cell antitumor immunity and immunotherapy.DiscussionOur study highlights a potential risk of CBD use in cancer patients and underscores the need for further investigation into its immunological effects and signalling mechanisms.